(untitled) (Global Media Journal - German Edition, 2015)
Recent developments in German television programming represent Adolf Hitler and his Nazi regime through comedic entertainment. While these programs do not poke fun at the Holocaust itself, they are utilizing the image of Hitler for parodistic purposes. Similar to existing foreign media depicting Hitler as a foolish ruler with farcical mannerisms, newer programs such as the comedy show Switch Reloaded and the movie Hotel Lux show a clumsy and gullible Hitler. This essay argues that these recent representations of Hitler are contributing to the ongoing cultural conversation of the Holocaust, while also encouraging new ways in how Germans can culturally cope with their recent past. Drawing on parody and cultural trauma research, this essay offers evidence from German national media reviews and newspaper articles.